ANALISIS NILAI DEPLESI DARI PRODUKSI HASIL HUTAN DI KABUPATEN TANAH LAUT - Aulia Rahmah; M Anshar Nur (PPJP Universitas Lambung Mangkurat, 2020)
This research aims to analyze development of depletion value, PSDH revenue, and comparison of depletion value with PSDH from production of forest products in Tanah Laut Regency. Data collection techniques are documentation from previous research, online, and instansional surveys. Data is processed by mathematical calculations using depletion formula, then compared to PSDH revenue. The result of research showed that ups and downs depletion value were depending on volume of round wood. Depletion per unit of round wood production of natural forests is bigger than plantation forests. Realization of PSDH received by Tanah Laut Regency is smaller than PSDH that should be accepted which is about 28,73 percent. Depletion value of rounded wood is bigger than PSDH value was received. PSDH value is only 1,55 percent of total round wood depletion (Rp. 40.427.004.997,70).Keywords: Sustainable Development, Forest Resources, Depletion, PSDH, Tanah Laut.